Hello!
We can solve in just two or three steeps:
![(6)/(7) x+(1)/(2) =(7)/(8) \\\\\\(6)/(7) x =(7)/(8) - (1)/(2)\\](https://img.qammunity.org/2020/formulas/mathematics/middle-school/1zk9rlunfphlat48lu6vnl05asht1awm0f.png)
There are a lot of ways to sum or difference fractions, but we can solve it using the easiest way.
First, we need to multiply the first fraction numerator by the second fraction denominator
Second, we need to multiply the first fraction denominator by the second fraction numerator
Third, we need to solve the operation depending if it's a sum or a difference
Fourth, we have to multiply the denominator of each fraction and it will be our new fraction denominator
Knowing that we have that
![(7)/(8) - (1)/(2)= (14-8)/(16) =(6)/(16) =(3)/(8)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/6q40aqhd854apj6r1wlwvby11rhc0ba4v2.png)
So,
![(6)/(7)x= (3)/(8)\\\\x=(3)/(8) *(7)/(6) =(21)/(48)= (7)/(16)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/xppdi79opcrhef3o2mk3l5jqz49z1bjcst.png)
Have a nice day!